Robert Troup correspondence - Troup, Robert, 1757-1832.
Five letters written by Troup to Aaron Burr (1780 January 16-October 23), two (1807 May 4 and 1809 August 23) to Benjamin Walker, and one each to Simeon De Witt (1812 January 31), John V. Henry (1818 December 26), and Morris S. Miller (1820 April 29) relating to New York state and national politics.
Soldier, jurist, and land agent.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Burr, Aaron, -- 1756-1836 -- Correspondence; Walker, Benjamin, -- 1753-1818 -- Correspondence; De Witt, Simeon, -- 1756-1834 -- Correspondence; Henry, John V. -- Correspondence; Miller, Morris S. -- 1779-1824 -- Correspondence; New York (State) -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1783-1865.; Jurists; Land agents; Soldiers